Development of a 1550 nm LiDAR System Using Galvanometer and i-ToF Method for Distance Measurement and 2D Object Reconstruction - Hutagalung, Febrian Winston; Purnamaningsih, Retno Wigajatri; Nainggolan, Sahat Pandapotan; Rofianingrum, Mefina Yulias; Hapiddin, Asep; Hanto, Dwi (Universitas Indonesia, 2025)
LiDAR (Light Detection and Ranging) is a high-precision distance measurement technology based on laser light reflection. This study develops a galvanometer-based LiDAR system utilizing the indirect Time of Flight (i-ToF) method with 100 MHz sinusoidal modulation and a 1550 nm eye-safe laser diode. The system is designed to measure distance and identify the shape of 2D objects. The system was tested through phase difference measurements, galvanometer response, and flat-surface mapping at distances of 25 cm and 35 cm. The measurement results demonstrate high linearity and stability up to a maximum range of 1.5 meters, in accordance with the 360° phase difference (∆φ) limitation. The measurements of object dimensions in the form of an aluminum foil-covered plate at distances of 25 cm (1.76 cm × 2.63 cm) and 35 cm (2.45 cm × 3.66 cm) indicate that increasing the distance between the object and the system results in a wider coverage area but with reduced spatial resolution. At a distance of 25 cm, the light beam shifts by 0.436 cm/1°∆φ, whereas at 35 cm it shifts by 0.611 cm/1°∆φ. Furthermore, the limited active area of the photodetector was identified as the main factor restricting the detection coverage. This research opens opportunities for further development, particularly in optimizing galvanometer angle adjustments and enhancing the photodetector’s active area to expand coverage and improve measurement accuracy under various operating conditions.